Agonistic Anti-PDGF Receptor Autoantibodies from Patients with Systemic Sclerosis Impact Human Pulmonary Artery Smooth Muscle Cells Function In Vitro - Svegliati, Silvia; Amico, Donatella; Spadoni, Tatiana; Fischetti, Colomba; Finke, Doreen; Moroncini, Gianluca; Paolini, Chiara; Tonnini, Cecilia; Grieco, Antonella; Rovinelli, Marina; Funaro, Ada; Gabrielli, Armando (Frontiers in Immunology, 2017)
ABSTRACT One of the earliest events in the pathogenesis of systemic sclerosis (SSc) is microvasculature damage with intimal hyperplasia and accumulation of cells expressing PDGF receptor. Stimulatory autoantibodies targeting PDGF receptor have been detected in SSc patients and demonstrated to induce fibrosis in vivo and convert in vitro normal fibroblasts into SSc-like cells. Since there is no evidence of the role of anti PDGF receptor autoantibodies in the pathogenesis of SSc vascular lesions, we investigated the biologic effect of agonistic anti PDGF receptor autoantibodies from SSc patients on human pulmonary vascular smooth muscle cells and the signaling pathways involved. The synthetic (proliferation, migration and type I collagen gene 1chain expression and contractile (smooth muscle-myosin heavy chain and smooth muscle-calponin expression) profiles of human pulmonary artery smooth muscle cells were assessed in vitro after incubation with SSc anti PDGF receptors stimulatory autoantibodies. The role of reactive oxygen species, NOX isoforms and mechanistic target of rapamycin (mTOR) was investigated. Human pulmonary artery smooth muscle cells acquired a synthetic phenotype characterized by higher growth rate, migratory activity, gene expression of type I collagen gene 1chain, and less expression of markers characteristic of the contractile phenotype such as smooth muscle-myosin heavy chain and smoth muscle-calponin when stimulated with PDGF and autoantibodies against PDGF receptor, but not with normal IgG. This phenotypic profile is mediated by increased generation of reactive oxygen species, expression of NOX4 and mTORC1. Our data indicate that agonistic anti PDGF receptor autoantibodies may contribute to the pathogenesis of SSc intimal hyperplasia.